Twin anemia polycythemia sequence: a single center experience and literature review. (October 2016) - Moaddab, Amirhossein; Nassr, Ahmed A.; Espinoza, Jimmy; Ruano, Rodrigo; Bateni, Zhoobin H.; Shamshirsaz, Amir A.; Mandy, George T.; Welty, Stephen E.; Erfani, Hadi; Popek, Edwina J.; Belfort, Michael A.; Shamshirsaz, Alireza A.
Abstract: Twin anemia polycythemia sequence (TAPS) is defined by significant intertwin hemoglobin discordance without the amniotic fluid discordance that characterizes twin–twin-transfusion syndrome (TTTS) in monochorionic twin pregnancies. TAPS is an uncommon condition which can either occur spontaneously, or following fetoscopic laser ablation for TTTS. This complication is thought to result from chronic transfusion through very small placental anastomoses; however, the pathogenesis of TAPS remains unknown. Consequently, there is no consensus in the management of TAPS. In this article, three cases of TAPS are described and we review the literature on this uncommon pregnancy complication.